Perception of Students on Tablet and Laptop Distribution Scheme of U.P. Government - Zaffar Ahmad Nadaf; Iffat Khan (LED Edizioni Universitarie, 2017)
If the 18th century is characterized as the age of reason, the 19th as one of industry and the 20th as revolution then the 21th century could well be known as the age of ICT. This is the time when more youth everywhere are involved in acquiring new knowledge and skills continuously throughout their lives and from virtually every context of daily life. This study aims at studying the effectiveness of a program of the government through students' perception. The scheme aimed at providing free tablet and laptops to the high school and senior secondary government school graduates. The sample consisted of 200 secondary and senior secondary boys and girls. The overall results revealed that there is favourable perception of students towards tablet and laptop distribution scheme of U.P. Government. Students' perception on the bases of level of schooling (level 1-class 10th and level 2-class 12th), gender and locale was also examined in the present study.